Strain Sweep Fatigue Testing of Sand Asphalt Mortar to Investigate the Effects of Sample Geometry, Binder Film Thickness, and Testing Temperature. Issue 10 (October 2021) - de Rezende, Lilian Ribeiro; Kommidi, Santosh Reddy; Kim, Yong-Rak; Khedmati, Mahdieh
This study evaluated the viscoelastic fatigue behavior of binder using strain sweep fatigue testing of cylindrical sand asphalt mortar (SAM) samples. The SAM samples can represent the realistic film thickness (such as 10–70 μm thick) of the binder in mixtures, while testing repeatability-efficiency can still be met as a result of the use of a standard sand as a load carrier between binder films. A proper testing protocol is still under development, and one of the unknowns in the field is a set of testing conditions that can provide repeatable and case-sensitive test results. Toward that end, SAM samples with different dosages of binder in three geometries were tested at varying temperatures in this study. A PG 64-34 binder was used, and a strain sweep test using a dynamic shear rheometer was conducted to compare the test results from the different cases. Four parameters resulting from the SAM testing were examined: two accounting for material linear viscoelastic behavior and two accounting for fatigue damage characteristics. The parameters were incorporated with statistical analyses to quantitatively evaluate data variability and sensitivity influenced by the binder film thickness, SAM specimen geometry, and testing temperature. The coefficient of variation was less than 20% for all the cases, which indicated the validity of the SAM method attempted in this study. Results also indicated that fatigue behavior was independent of the SAM geometries used in this study, while binder film thickness and testing temperature significantly affected test results.